Dysphagia in multiple system atrophy consensus statement on diagnosis, prognosis and treatment. (May 2021) - Calandra-Buonaura, Giovanna; Alfonsi, Enrico; Vignatelli, Luca; Benarroch, Eduardo E.; Giannini, Giulia; Iranzo, Alex; Low, Phillip A.; Martinelli, Paolo; Provini, Federica; Quinn, Niall; Tolosa, Eduardo; Wenning, Gregor K.; et al.
Abstract: Multiple system atrophy (MSA) is a neurodegenerative disorder characterized by a combination of autonomic failure plus cerebellar syndrome and/or parkinsonism. Dysphagia is a frequent and disabling symptom in MSA and its occurrence within 5 years of motor onset is an additional diagnostic feature. Dysphagia can lead to aspiration pneumonia, a recognized cause of death in MSA. Guidelines for diagnosis and management of dysphagia in MSA are lacking. An International Consensus Conference among experts with methodological support was convened in Bologna to reach consensus statements for the diagnosis, prognosis, and treatment of dysphagia in MSA. Abnormalities of the oral and pharyngeal phases of swallowing, esophageal dysfunction and aspiration occur in MSA and worsen as the disease progresses. According to the consensus, dysphagia should be investigated through available screening questionnaires and clinical and instrumental assessment (videofluoroscopic study or fiberoptic endoscopic evaluation of swallowing and manometry) at the time of MSA diagnosis and periodically thereafter. There is evidence that dysphagia is associated with poor survival in MSA, however effective treatments for dysphagia are lacking. Compensatory strategies like diet modification, swallowing maneuvers and head postures should be applied and botulinum toxin injection may be effective in specific conditions. Percutaneous endoscopic gastrostomy may be performed when there is a severe risk of malnutrition and pulmonary complications, but its impact on survival is undetermined. Several research gaps and unmet needs for research involving diagnosis, prognosis, and treatment were identified. Highlights: Dysphagia is a frequent and disabling symptom in MSA. Dysphagia can lead to aspiration pneumonia, a cause of death in MSA. Consensus statements for diagnosis, prognosis, treatment of dysphagia are supplied. Unmet needs for research on dysphagia in MSA are also identified.